The weight-adjusted-waist index predicts all-cause and cardiovascular mortality in hypertension - Zheng, Yu; Nie, Zixing; Zhang, Yifan; Sun, Tao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWeight-adjusted-waist (WWI) is a novel indicator of obesity that reflects the degree of central obesity in the human body.ObjectivesThe study aimed to explore the relationship between WWI and mortality in hypertensive individuals.MethodsCross-sectional data from the 2001–2018 National Health and Nutrition Examination Survey (NHANES) dataset were used in this study. The relationship between WWI and mortality was assessed using a weighted Cox proportional risk model; the nonlinear relationship was explored using restricted cubic splines. The robustness of the results was verified by subgroup and sensitivity analyses.ResultsA cohort of 11,556 people with a diagnosis of hypertension was included in this study. As a continuous variable, WWI was linked to higher rates of mortality from all-cause (HR = 1.23, 95% CI = 1.14, 1.33) and cardiovascular disease (CVD) (HR = 1.43, 95% CI = 1.23, 1.66) with hypertension in Model 3 adjusted for variables. Using WWI as a tertile categorical variable, individuals in the highest tertile had a 33% higher risk of all-cause death (HR = 1.33, 95% CI = 1.14, 1.56) and a 65% higher risk of CVD death (HR = 1.65, 95% CI = 1.19, 2.27) than individuals in the lowest tertile. According to the subgroup analysis, almost all groups showed a consistent positive correlation between WWI and mortality related to all-cause and CVD.ConclusionIn adults with hypertension, there is a positive association between WWI and all-cause and CVD mortality.